Questions: Factor the polynomial completely.
[ y^2-1= ]
Transcript text: Factor the polynomial completely.
\[
y^{2}-1=
\]
Solution
Solution Steps
Step 1: Identify the Polynomial
We start with the polynomial \( y^{2} - 1 \).
Step 2: Recognize the Difference of Squares
The expression \( y^{2} - 1 \) can be recognized as a difference of squares, which follows the identity:
\[
a^{2} - b^{2} = (a - b)(a + b)
\]
where \( a = y \) and \( b = 1 \).
Step 3: Apply the Difference of Squares Formula
Using the difference of squares formula, we can factor \( y^{2} - 1 \) as follows:
\[
y^{2} - 1 = (y - 1)(y + 1)
\]
Step 4: Present the Fully Factorized Form
Thus, the fully factorized form of the polynomial \( y^{2} - 1 \) is:
\[
(y - 1)(y + 1)
\]